Skin Graft Review in Dermofasciectomy for Dupuytren’s Contracture within 48 Hours: Challenging Historical Practice - Ansari, Saif Akhter; Kennedy, James Andrew; Younis, Fizan (Journal of Hand and Microsurgery, 2021)
Introduction Early review of skin graft following dermofasciectomy with skin grafting for Dupuytren’s disease is not standard practice because of the potentially adverse effects on inosculation and neovascularization process of the skin grafting. The purpose of this retrospective case series was to observe whether early review of grafts postoperatively at 48 hours adversely affects graft survival and surgical outcomes.Materials and Methods Forty-nine primary and revision procedures were retrospectively analyzed for treatment outcomes, postoperative complications, functional hand scoring, and satisfaction rates postoperatively.Results Thirty-eight patients were treated successfully with no postoperative contracture. There were three treatment failures and two graft failures, with two amputations within these failures. Paired pre- and postoperative Unité Rhumatologique des Affections de la Main scoring demonstrated significant improvement in hand function for primary procedures, with a mean satisfaction score of 7.7 out of 10.Conclusion We have shown early graft review following dermofasciectomy and full-thickness skin grafting to be safe, allowing early mobilization and splinting, with our postoperative failure and complication rate being within published literature.
Keywords: Dupuytren’s disease; dermofasciectomy; skin graft; postoperative review